Memoirs and Letters of Polish Authors from the Western Krai (Lithuania, Belarus, Ukraine) from the period of 1795–1918 – A Summary of the Project’s Outcomes and Characteristics of Research Perspectives - Caban, Wiesław; Michalska Bracha, Lidia (Respectus Philologicus, 2018)
The article discusses the studies conducted in 2012–2017 at the Jan Kochanowski University under the research project entitled Memoirs and Letters of Polish Authors from the Western Krai (Lithuania, Belarus, Ukraine) from the Period of 1795–1918. The project was implemented under the National Programme for the Development of Humanities by an international research team led by Professor Wiesław Caban. The study included inventorying and cataloguing the 19th-century diaries, memoirs and collections of letters of Polish authors from the so-called Western Krai (Lithuania, Belarus, Ukraine) as well as the authors writing about these territories. Surveys of archival materials were conducted in libraries and archives in Lithuania, Belarus, Ukraine, Russia (including Siberia), London and Paris. The outcome of the project is an online database of memoirs and letters available at the Jan Kochanowski University website and a series of publications of the most valuable memoirs from Russian, Lithuanian and Ukrainian archives.
Keywords: History of the 19th Century; Memoirs and Letters of Poles of the 19th Century; Fate of Poles in Lithuania, Ukraine and Belarus